Occupational Stressors and Employee Performance in Service Sector of Lahore, Pakistan - Amber Imtiaz, Dr. Khalid Khan (Journal of Research in Humanities, 2023)
: In recent years, stress has emerged as a serious dilemma across all spheres of life particularly at work settings. The aim of the current research is to examine the relationship between occupational stressors (role ambiguity, role conflict, work overload) and employee performance in service sector of Lahore, Pakistan. While carrying out the study, the service sector was divided into four major categories on the basis of importance; i-e health, banking, educational, telecom and some other relevant service companies were selected with the help of stratified random sampling technique for data collection. Factor analysis and reliability test were applied to assess the questionnaire data. The primary data was collected from a sample of 350 respondents through self-administered questionnaires and the effective response rate was 88% which is highly acceptable. Further, for the purpose of data analysis, correlation, regression analysis and ANOVA tests were applied by using Statistical Package for Social Sciences (SPSS16.0).The findings and interpretations revealed a significant positive relationship between role ambiguity, work overload and employee performance. On the other hand, role conflict has no significant relation with employee performance. The results also indicated that out of the three selected determinants of stress, role ambiguity has a greater impact on performance of the employees. The current study is considered to be policy oriented as it would give an insight to various service organizations of Lahore that how to maintain a required level of stress in the organization that is responsible for the inefficiency of the employees at work place. Only Lahore city is selected for data collection